Market Expansion Opportunities for Nanjil Dairy Products in The Southern Tamil Nadu Region - Hanson, G. Jenit; M, Babima; Muhila, M. Gnana; Anand, S. T. (International Journal of Accounting and Economics Studies, 2025)
The Indian dairy sector plays a crucial role in rural livelihoods, nutritional access, and regional economic growth. Despite this, local dairy brands struggle to scale due to fragmented markets, weak branding, and distribution challenges. This study investigates the market expansion potential of Nanjil Dairy Products in Southern Tamil Nadu, focusing on consumer behaviour, supply chain dynamics, and brand positioning. Five core products—milk, curd, ghee, butter, and flavored milk—were studied using data from 540 respondents across Kanyakumari, Tirunelveli, Thoothukudi, Madurai, and Virudhunagar districts. Data collection involved structured questionnaires and field surveys. Analytical methods included Likert scale analysis, correlation matrix, and reliability assessment, and Structural Equation Modeling (SEM) to evaluate nine key factors: product quality, pricing, brand reputation, distribution network, packaging, promotional efforts, taste, nutritional value, and product variety. Five hypotheses were tested, exploring the influence of brand perception, distribution efficiency, price sensitivity, product variety, and promotional strategies on market reach. Results showed that Nanjil’s products are well-regarded for quality but face challenges in distribution reach and pricing competitiveness. According to the study, implementing targeted marketing campaigns that emphasize the quality of the product and its health benefits, improving pricing models, and bolstering distribution should be the main goals of strategic market expansion. These results give Nanjil Dairy useful advice on how to take advantage of unrealized potential and increase its market share in the dairy industry in Southern Tamil Nadu.
Keywords: Nanjil Dairy, Market expansion, consumer behaviour, Tamil Nadu, Structural Equation Modelling, Correlation matrix